Kiến trúc phố cổ Hội An - Việt Nam - Phan Huy Lê, GS.; Trần Thị Quế Hà,; Lê Huy,; Nguyễn Văn Kim, (Thế giới, 2003)
Phố cổ Hội An trong lịch sử; Kiến trúc truyền thống Hội An; Ngôi nhà truyền thống, cuộc sống hiện đại.